The role of cellular adhesion molecule in the development of proliferative diabetic retinopathy - Adamiec, Joanna; Oficjalska-Młyńczak, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Development of proliferative diabetic retinopathy`s pathogenesis is still unknown. Last years publications seems to show immuno-inflammatory base of structural and functional retinal vessels endothelial cells's changes. Chronical retinal ischemia leads to development of pathological vessels and formation of fibrovascular tissue at the vitreoretinale interface. One of the important cause of the damage is leukocytes activation and adhesion to vascular endothelium, that is mediated by the specific adhesion molecules. Increase of soluble cellular adhesion molecules (CAMs) in serum, vitreous, epiretinal membranes of patients with PVR seems to confirm its role in the pathogenesis of this process. This publication attempts to estimate the CAM's role in progression of PDR.